Chinese herbal formulas for treating hypertension in traditional Chinese medicine: perspective of modern science - Xiong, Xingjiang; Yang, Xiaochen; Liu, Yongmei; Zhang, Yun; Wang, Pengqian; Wang, Jie (Hypertension research, 2013)
Hypertension, which directly threatens quality of life, is a major contributor to cardiovascular and cerebrovascular events. Over the past two decades, domestic and foreign scholars have agreed upon various standards in the treatment of hypertension, and considerable progress has been made in the field of antihypertensive drugs. Oral antihypertensive drugs represent a milestone in hypertension therapy. However, the blood pressure standard for patients with hypertension is far from satisfactory. The study of Chinese herbal formulas for treating hypertension has received much research attention. These studies seek to integrate traditional and Western medicine in China. Currently, Chinese herbal formulas are known to have an outstanding advantage with regard to bodily regulation. Research shows that Chinese medicine has many protective mechanisms. This paper addresses the process of the antihypertensive mechanisms in Chinese herbal formulas for treating hypertension. These mechanisms are to be discussed in future research.